Systemic therapy with individuals - Boscolo, Luigi (Systemic thinking and practice series., 1996)
Until recently, systemic therapy has been identified with family therapy. This no longer applies; the systemic approach and its techniques can now be used - with profit - in therapy with individuals. This book introduces and describes the first adaptation of the systemic model to the individual context.